Sex Differences in Rat Intervertebral Disc Structure and Function Following Annular Puncture Injury. Issue 18 (15th September 2019) - Mosley, Grace E.; Hoy, Robert C.; Nasser, Philip; Kaseta, Timothy; Lai, Alon; Evashwick-Rogler, Thomas W.; Lee, Michael; Iatridis, James C.
Abstract : Study Design: A rat puncture injury intervertebral disc (IVD) degeneration model with structural, biomechanical, and histological analyses. Objective: To determine if males and females have distinct responses in the IVD after injury. Summary of Background Data: Low back pain (LBP) and spinal impairments are more common in women than men. However, sex differences in IVD response to injury have been underexplored, particularly in animal models where sex differences can be measured without gender confounds. Methods: Forty-eight male and female Sprague Dawley rats underwent sham, single annular puncture with tumor necrosis factor α (TNFα) injection (1×), or triple annular puncture with TNFα injection (3×) surgery. Six weeks after surgery, lumbar IVDs were assessed by radiologic IVD height, spinal motion segment biomechanical testing, histological degeneration grading, second harmonic generation (SHG) imaging, and immunofluorescence for fibronectin and α-smooth muscle actin. Results: Annular puncture injuries significantly increased degenerative grade and IVD height loss for males and females, but females had increased degeneration grade particularly in the annulus fibrosus (AF). Despite IVD height loss, biomechanical properties were largely unaffected by injury at 6 weeks. However, biomechanical measures sensitive to outer AF differed by sex after 3× injury—male IVDs had greater torsional stiffness, torque range, and viscoelastic creep responses. SHG intensity of outer AF was reduced after injury only in female IVDs, suggesting sex differences in collagen remodeling. Both males and females exhibited decreased cellularity and increased fibronectin expression at injury sites. Conclusion: IVD injury results in distinct degeneration and functional healing responses between males and females. The subtle sex differences identified in this animal model suggest differences in response to IVD injury that might explain some of the variance observed in human LBP, and demonstrate the need to better understand differences in male and female IVD degeneration patterns and pain pathogenesis. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the textA rat annular puncture model assessed sex effects on intervertebral disc structure, biomechanics, and histology 6 weeks after injury. Subtle, but distinct, degeneration, and injury responses were observed between males and females, suggestive of greater fibrotic response in males. Future intervertebral disc research should consider possible sex effects.